Preparación de circonia sulfatada promovida con aluminio con actividad catalítica para la isomerización del butano y heptano (2007)
ABSTRACT: In this research project a simple method have been proposed for the synthesis of Alpromoted sulfated zirconia catalysts, by impregnation of commercial hydrous zirconia whit aqueous solutions of Al 2 (SO 4 ) 3 , furthermore of catalysts without promoter, obtained from ammonium sulfate. In agreement with the proposed synthesis method, the characterization results suggest that Al 3+ and SO 4 2species supplied by the precursor are mainly located on the surface of the zirconium oxide, where Al 3+ provides structural stability to the zirconium oxide, whereas the sulfate groups are responsible for the formation of the active sites for the hydrocarbon activation.